Boycott in Hadith Perspective: History and Implementation - Andaluzi, Fahmi; Alif, Muhammad; Wahid, Abd; Faiz, Muhammad (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
This article aims to explore the practice of boycotting during the Prophet's time, including whether it was carried out by the Prophet, his Companions, or the opposition. It also investigates whether hadith, as an authoritative source in Islam, supports boycotting and how to contextualize these teachings in the present. This research employs a library-based approach, collecting data from hadith, books, and scholarly articles relevant to the topic. The methods used include takhrij hadith and descriptive-analytical processing of historical accounts of boycotting during the Prophet's era to describe and analyze its contemporary application. The study finds that boycotting practices existed during the Prophet's time and were carried out by the Prophet and his Companions. Implementing hadith on boycotting in the modern context is complex but remains relevant to issues such as war and blasphemy. Additionally, contemporary boycotts have evolved into moral support actions at individual and international levels, aimed at drawing attention and resolving conflicts. Muslim scholars, institutions, and religious organizations consider boycott rulings based on fraternal hadith, the prohibition of oppression, and ijtihad through Islamic legal approaches (fiqh and ushul fiqh), such as Syadd al-Żarāi' and Qiyās. These considerations integrate textual evidence with modern contexts, ensuring flexible and dynamic rulings that align with the objectives of Islamic law (maqāṣid al-sharīʻah), particularly justice and welfare for the ummah.